An Analysis on the Effect of Television Show on the Students’ Character of Elementary School Students in Bangkinang Kota - Mufarizuddin, Mufarizuddin; Fauziddin, Mohammad (Jurnal Pendidikan Indonesia, 2017)
It is found that some elementary school students favor to talk and behave one of the cinema, namely "Anak Jalanan". The cinema influences the children’s character, in this case in high school classes such as imitating fashion style, speech style, even hairstyles. Such kinds of imitating are still in a good control. However, there is an increasing on fear of the worst development of moral. This research is aimed at: (1) to analyze the possibility effect of cinema on behavior changing of elementary school students in Bangkinang Kota, (2) to analyze the factors causes the changing of the character, and 3) to give the information on the importance of assisting the children while watching TV. The subjects of the research were elementary school students in Bangkinang Kota, in academic year 2016/2017. The data were collected by documentation, questionnaire, and interview guide. The findings showed that cinema Anak Jalanan have significant effect on the changing of children’s character. It is highly exoected that parents play the role of assisting the children.